The Impact of Flexible Organizational Structure on Universities Employee’s Performance and the Moderated Role of Commitment Culture - Esraa Awawdeh (2025)
In today's volatile environment, where effective interaction with organizational structures is essential, flexibility plays a pivotal role in providing organizations with a competitive edge. This research aims to investigate how the flexibility of organizational structures impacts the performance of employees in universities in the UAE, moderated by commitment culture. This quantitative study tests a hypothesized model using data from 100 university employees. The findings indicate that flexible organizational structure significantly influences employee performance; an increase in organizational flexibility correlates with enhanced employee performance. However, the study reveals that commitment culture does not strengthen the relationship between flexible organizational structure and employee performance.